PENGARUH EKSTRAK DAUN C.ODORATA TERHADAP PROSES KESEMBUHAN LUKA INSISI PADA TIKUS SPRAGUE-DAWLEY - Ni Sri Yuliani; Victor Lenda (JURNAL KAJIAN VETERINER, 2019)
Chromolaena odorata (kirinyu/sufmuti) is a species of weed which utilized as traditional medicine especially for wound healing. This research was conducted to study the histological effect of C.odorata leaf extract to healing process of incision wound in Sprague-Dawley rats. A total of 45 males - 6 weeks of Sprague Dawley rats at 150-200g body weight were utilized in this study. Those rats were divided into five groups, basis ointment, Betadine 10%, C.odorata 5%, C.odorata 10%, and C.odorata 20%. All groups of rats were given a 3 cm long linear incision at dermal depth on the backs. The extract and medication were topically applied once a day for ten days. 3 rats of each group were euthanized in day 2, 6, and 10 after incision. Subsequently, skin tissue was obtained and fixated in 10% buffer formalin for Hematocixylin - Eosin staining. The measured variables were wound healing both macroscopical and microscopical figures from day 0 to day 10 after incision. Data were analyzed descriptively. Microscopic observation showed that various concentrations of C.odorata extracts affected wound healing process. C.odorata Extract is allegedly able to stimulate wound healing by increasing fibroblasts for re-epithelization.